MANAJEMEN KONFLIK DALAM PENYELESAIAN PERMASALAHAN HUBUNGAN INDUSTRIAL BERDASARKAN UU NO 2 TAHUN 2004 DI PT. DEWASUTRATEX - Resya Dwi Marselina; Cici Rahma Damayanti; Isti Septiani; N. Hilmi Kurotul Aenin; Rahmat Hidayat; Rosa Lianawati (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Work is one of the most important things that is very closely related to human life because with work people will get wages to meet their living needs, workers need work from entrepreneurs, entrepreneurs also need the role of workers to carry out production activities, this is known as the relationship between workers and companies. Every interaction that occurs in the relationship between workers and companies will give rise to differences of opinion or thoughts between workers and company management which will give rise to industrial relations conflicts. Smooth and harmonious industrial relations between employers and workers are the main factor in preventing industrial relations disputes, including employment termination (PHK) disputes. Every interaction that occurs in the relationship between workers and companies will give rise to differences of opinion or thoughts between workers and company management which will give rise to industrial relations conflicts. In this case, employers and workers are expected to be able to resolve conflicts that occur within the company in a manner that is in accordance with employment recommendations. Industrial relations disputes are regulated in Law Number 2 of 2004 concerning PPHI (Settlement of Industrial Relations Disputes) and can be resolved through the courts (judicial) and outside the courts (non-judicial). The parties are free to decide how to resolve labor disputes. The aim of writing this article is to understand conflict management in resolving industrial relations problems based on Law no. 2 in 2004. Keywords: Industrial, Conflict, Management, Law, Workers.